Development of the Hanjeli Tourism Village Website as a Platform Digital for Managers and Tourists - vany octaviany; Ranita Windriani (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Hanjeli Tourism Village, located in Sukabumi Regency, West Java, has great potential for developing nature-based tourism and local culture, particularly through its superior commodity, the hanjeli plant. However, the village faces significant challenges in terms of promotion and management of tourism information, which still relies on conventional methods. This community service activity (Abdimas) aims to increase the competitiveness of Hanjeli Tourism Village by developing a website as an integrated digital platform. This website is designed to improve the accessibility of tourism information, simplify the process of booking tour packages, and promote destinations and local products based on hanjeli. The website's main features include information on tourist destinations, homestays, photo galleries, and local products based on hanjeli plants. The website development is also accompanied by training for village managers to improve their digital and managerial skills in managing this platform effectively. The implementation of this website is expected to increase the number of tourist visits, introduce untapped tourism potential to its full potential, and empower the local community in digital management and online marketing. Furthermore, this website also serves as a platform to promote locally made hanjeli-based products, such as snacks, health drinks, and handicrafts, managed by the village's MSME group. Through website development and digital training, it is hoped that the capacity of the Hanjeli Tourism Village community will be increased in managing and promoting local products more professionally and efficiently.